Partners with God Theological and Critical Readings of the Bible in Honor of Marvin A. Sweeney - Birdsong, Shelley L.; Frolov, Serge (Claremont Studies in Hebrew Bible and Septuagint, 2017)
A set of critical readings of the Pentateuch and Prophets in the Hebrew Bible